Allosteric regulation of tRNA import: interactions between tRNA domains at the inner membrane of Leishmania mitochondria - Goswami, Srikanta (Oxford University Press, 2003)
Import of nucleus-encoded tRNAs into the mitochondria of the kinetoplastid protozoon Leishmania involves recognition of specific import signals by the membrane-bound import machinery. Multiple signals on different tRNA domains may be present, and further, importable RNAs interact positively (Type I) or negatively (Type II) with one another at the inner membrane in vitro. By co-transfection assays, it is shown here that tRNA(Tyr) (Type I) transiently stimulates the rate of entry of tRNA(Ile) (Type II) into Leishmania mitochondria in transfected cells, and conversely, is inhibited by tRNA(Ile). Truncation and mutagenesis experiments led to the co-localization of the effector and import activities of tRNA(Tyr) to the D domain, and those of tRNA(Ile) to the variable region–T domain (V-T region), indicating that both activities originate from a single RNA–receptor interaction. A third tRNA, human tRNA(Lys), is imported into Leishmania mitochondria in vitro as well as in vivo. This tRNA has Type I and Type II motifs in the D domain and the V-T region, respectively, and shows both Type I and Type II effector activities. Such dual-type tRNAs may interact simultaneously with the Type I and Type II binding sites of the inner membrane import machinery.